Simile and meaning sentences relating to "tree" - Chuluun, Byambatsetseg (Mongolian Journal of Humanities and Social Sciences, 2024)
When looking at the linguistic evidence for the metaphor "tree", there are cases where it is used to compare time, creatures and animals, writing instruments, and objects and organs made of wood. A tree consists of a stem, roots, branches, and twigs, and there are cases where objects are named by their hidden nature, as metaphors within the context of words that indicate their characteristics and appearance. In the genre of oral storytelling, the positive value and attitude of the main characteristics of trees, such as growth and reproduction, and the importance of nature and ecology, are often repeated in magical tales as "guides", "symbols of growth", “sustainers of life", “worship of trees” and “analyzing through trees” define the environment of the metaphorical character of a tree. “Мод”-той холбоотой зүйрлэхүүн ба утгын өгүүлэмж Хураангуй: Энэхүү өгүүлэлд монгол хэлний хэвшмэл хэллэгт багтах аман зохиолын жижиг төрөл оньсого, хүүрнэн өгүүлэх аман зохиолын төрөл болох явган үлгэрээс “мод” хэмээх зүйрлэлээр илэрч буй ухагдахууныг хэл, соёл, утга зүйн талаас нь авч үзэж байна. Монгол хэлэн дэх хэлц үг хэллэгт аливаа ард түмний соёл, үндэсний сэтгэлгээ, зан заншил, газар нутгийн байршил, ахуй амьдралын онцлог гэх мэт угсаатны өвөрмөц онцлогийг өөртөө агуулсан байдгаас гадна ихэнх нь юм үзэгдлийг шууд ба шууд бусаар заан нэрлэдэг онцлогтой юм. Иймд “мод” хэмээх зүйрлэлээр илэрч буй ухагдахууныг орон ба утгын хүрээнд задлан тайлбарлахыг зорив. Түлхүүр үг: цаг хугацааг зүйрлэх, амьтныг зүйрлэх, бичгийн хэрэгсэл, эд юмс, эд эрхтний нэр, утга зүй, орны ай